Preschool education in Brazil: does public supply crowd out private enrollment? - Bastos, Paulo (2013)
We examine if an expansion in the supply of public preschool crowds-out private enrollment using rich data for municipalities in Brazil from 2000-2006, where federal transfers to local governments change discontinuously with given population thresholds. Results from a regression-discontinuity design reveal that larger federal transfers lead to a significant expansion of local public preschool services, but show no effects on the quantity or quality of private provision. These findings are consistent with a theory in which households differ in willingness-to-pay for preschool services, and private suppliers optimally adjust prices in response to an expansion of lower-quality, free-of-charge public supply.